Prospect Theory and Risk-Return Relationship: Evidence from Chinese Listed Companies - Liao, Aijing (2014)
With the fast development of economy, China has drawn much attention from foreign businesses and scholars in recent decades. The special condition and cultural environment of the country has been keeping businesses in the country different from the situations in other parts of the world.